COVID-19 and Change - Goede, Miguel (Archives of Business Research, 2020)
Purpose – The purpose of this article is to identify and describe the changes that have taken place or are taking place throughout our societal structures as a consequence of the COVID-19 pandemic crisis. Methodology – The paper draws from published articles and papers that have reported on the changes caused by the COVID-19 pandemic in many different areas of research to assemble a larger picture of the overall impact. Findings – The onset and evolution of the COVID-19 pandemic has revealed systemic vulnerabilities in a wide variety of areas, from the world order and the economy to the delivery of health care and the way families function. Given the size and magnitude of the disruptions, returning to pre-COVID-19 conditions is not an alternative. The crisis has accelerated many trends, while muting or slowing others. It has enhanced the shift of the centrum of power from the West to the East. Many countries have begun to think locally again, especially regarding supply chains and food security. The role of government has increased on a range of fronts. Digitalization has increased as the concept of ‘social distancing’ and functioning remotely has become the new normal. Originality – Over a relatively short period since the pandemic began, many studies on the impact of the pandemic have been published, though they have been largely focused on specific topics. By contrast, the aim of this research was to compile these various impacts to better understand the bigger picture as these dramatic changes are interwoven into our daily lives. Keywords – COVID-19, World Order, Globalization, Capitalism, Neoliberalism, Governance, Civil right, Climate change, Economy, Science, Food security, Future of Work, Cryptocurrency, Healthcare, Family structures, Learning, Travel, Mass gathering Conclusions – The pandemic has and will continue to change the world in many areas and in many ways.